Diversity of antimicrobial resistance and virulence genes of pathogenic Escherichia coli recovered from pigs in England - Connelly, Samuel A. M.; AbuOun, Manal; Duggett, Nicholas; Kirchner, Miranda; Navickaite, Indre; Nunez-Garcia, Javier; Williamson, Susanna; Vaughan, Kelly; Teale, Christopher; Anjum, Muna F. (Frontiers in Microbiology, 2025)
IntroductionWe characterised the genomes of 208 pathogenic Escherichia coli isolated from pigs diagnosed with enteric colibacillosis (EC), bowel oedema (BO) or colisepticaemia (CS) in England between 2016–2020 to investigate their antimicrobial resistance (AMR) and virulence-associated genes (VAGs).MethodsAMR and VAGs were identified using the APHA SeqFinder tool, while SNP comparisons were performed with Snippy and RAxML-NG. A subset of isolates were long-read sequencing to examine mobile genetic elements.ResultsThe EC group primarily carried fimbrial and toxin genes, including faeG (F4, 33%) and stb (STb, 48%). The BO group primarily encoded fedF (F18, 38%) and stx2e-AB (Stx2e, 38%). The CS group were more homogeneous, with over 70% harbouring genes for curli fibre (csgABGFE), haemolysin, iss, iron transport (sitABCD), and siderophore (iucABCD, iroBCDEN) genes. Overall, 62% of isolates were multidrug resistant (MDR) with the Enterotoxigenic E. coli (ETEC) showing an MDR prevalence of 73%. Phylogenetic analysis identified two high-risk sequence types (STs), ST90 and ST772; both unique to juvenile pigs and previously under-reported in the UK. Plasmid analysis of representative ETECs from these STs revealed large MDR plasmids potentially co-linked with metal and disinfectant resistance genes.DiscussionThis study highlights the predominant AMR and VAGs in pathogenic E. coli from diseased pigs in England, the emergence of high-risk lineages, and the role of mobile genetic elements in resistance dissemination. These findings improve understanding of pathogenic E. coli in pigs and support efforts to improve diagnostics, guide treatment, and control of farm outbreaks.